Do protocols for new randomised trials take previous similar trials into account? Cohort study of contemporary trial protocols - Asger Sand Paludan-Müller; Peter Christian Gøtzsche; Michelle C Ogden; Mikkel Marquardsen; Jonas Vive; Karsten Juhl Jørgensen (BMJ Open)
Objective To investigate to what extent evidence from previous similar trials or systematic reviews was considered before conducting new trials.Design Cohort study of contemporary protocols for trials with ethical approval.Methods All protocols for randomised trials approved by the five ethical committees in Denmark between January 2012 and March 2013 were screened for eligibility. Included protocols were read in full to determine whether a systematic search had been conducted and references were checked to evaluate whether trial rationale and design could be challenged for not adequately considering previous evidence. To investigate whether protocols cited relevant trials, we used simple search strategies that could easily be conducted by researchers without experience with literature searches.Results Sixty-seven protocols were included. Only two (3%) of the protocols explicitly stated to have conducted a literature search and only one (1%) provided information that allowed the search to be replicated. Eleven (16%) of the protocols described trials where we found the information insufficient to judge if the trial was ethically justified, either due to a comparator that was not supported by the presented evidence (six protocols), because they did not present a rationale for conducting the trial (two protocols), or for both reasons (three protocols). For eight (12%) of the protocols, our search identified trials that could have been relevant to cite as justification.Conclusions While most protocols seem to adequately consider existing evidence, a substantial minority of trials might lack a sufficient evidence base. Very few trials seemed to have been based on a literature search which makes it impossible to know whether all relevant previous trials had been considered. Rules for ethical approval should include requirements for systematic literature searches to ensure that research participants are not exposed to sub-optimal treatments or unnecessary harms as well as to reduce research waste.